Study on Longitudinal Ship Strength Caused by the Placement of Beams and Girders on Upper Deck Side - Andi Ardianti; Andi Mursid Nugraha; Ganding Sitepu; Hamzah Hamzah; Ade Khantari; Suandar Baso (EPI International Journal of Engineering, 2018)
The location of the beam and the deck girder of the ship can be effect on it is strength especially for the longitudinal strength due to the vertical wave bending moment. The objective of this study is to know the structural response of the ship due to vertical bending moment load on hogging and sagging conditions. The analysis is carried out by using Finite Element Method so-called ANSYSTM. The results shows that the stress occurring on the ship model with deck beam above the deck plate is larger than the ship model with deck beam under the deck plate. When the load with the variated of 0.2 x moment of vertical moment load, there is an increase of stress that occurs both on the deck area about 12% while on the bottom area about 0.98%. This study also conducted a stress comparison by using analysis methods with analytical methods. The results show that by the Stress differences that occur in the structure with the longitudinal deck beam and deck girder above are 14.1% on the deck and 7.1 on the bottom. Whereas in the structure with deck longitudinal deck eam and deck girder under there is a difference of 5.7% on the deck area and 3.5% in the bottom area of the ship. The stress that occur in both models have a difference that is not too far away and still under the permisible stress by the classification society so that both can be applied to the construction of a tanker.